The role of epitexts in drama translation - Braga Riera, Jorge (The Journal of Specialised Translation, 2018)
In recent years, the notion of paratranslation has grown in Translation Studies, particularly in the literary field. Nevertheless, little attention has been paid to the effect that paratextual components — peritextual and epitextual — (Genette 1997) may have on the rendering of theatrical texts into another language, especially if these texts are intended for performance. This article will seek to deal with the issue of paratranslation in the theatre, and more specifically with the potential influence of epitexts on the reception of a particular stage play in a different culture, as well as with the significance of the figure of the translator in the process. Two recent British performances of the Spanish classic Life is a Dream, based on two different translations, have been used by way of example. The results will show how reviews, webpages, videos, posters, flyers and programmes can add to the manner in which a particular play is perceived in the eyes of its target audiences, and to what extent the final outcome may be felt as part of the recipient theatrical culture.